Medicalization of Social Problems - Ashley Frawley (Handbook of the Philosophy of Medicine, 2015)
Medicalization, a key concept in sociology, refers to the process by which personal and social phenomena are increasingly understood in medical terms. Constructionist approaches to social problems have made considerable use of the medicalization thesis to examine the ways medical language is used to describe a wide variety of social problems. This chapter describes the medicalization process, use of the concept in social problems constructionist research, and causes and contexts of the ascendance of medical language in social problem rhetoric. The broader social benefits and consequences of increasing medicalization of social problems are also discussed.